2003
DOI: 10.1074/jbc.m300770200
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Remodeling Activities Act on UV-damaged Nucleosomes and Modulate DNA Damage Accessibility to Photolyase

Abstract: Nucleosomes inhibit DNA repair in vitro, suggesting that chromatin remodeling activities might be required for efficient repair in vivo. To investigate how structural and dynamic properties of nucleosomes affect damage recognition and processing, we investigated repair of UV lesions by photolyase on a nucleosome positioned at one end of a 226-bp-long DNA fragment. Repair was slow in the nucleosome but efficient outside. No disruption or movement of the nucleosome was observed after UV irradiation and during re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 66 publications
(101 reference statements)
2
53
0
Order By: Relevance
“…50 for review). Finally, previous work has demonstrated that protected lesions in nucleosomal DNA can be exposed to nucleotide excision repair enzymes or UV photolyase by the addition of ATP-dependent remodeling factors in vitro (51)(52)(53). Although no direct interaction has been shown between pol ␤ and a nucleosome remodeling factor, proteins such as XRCC1, WRN, and͞or PARP may mediate such an interaction.…”
Section: Discussionmentioning
confidence: 98%
“…50 for review). Finally, previous work has demonstrated that protected lesions in nucleosomal DNA can be exposed to nucleotide excision repair enzymes or UV photolyase by the addition of ATP-dependent remodeling factors in vitro (51)(52)(53). Although no direct interaction has been shown between pol ␤ and a nucleosome remodeling factor, proteins such as XRCC1, WRN, and͞or PARP may mediate such an interaction.…”
Section: Discussionmentioning
confidence: 98%
“…BAF47-deficient cells are hypersensitive to genotoxic stress (Klochendler-Yeivin et al, 2006), and re-expression of BRG1 in BRG1-deficient SW13 cells renders the cells resistant to ultravioletinduced DNA damage (Gong et al, 2008). SWI/SNF facilitates the repair of cyclobutane pyrimidine dimers (Gaillard et al, 2003) and acetylaminofluorene-guanine adducts (Hara and Sancar, 2002) in a nucleosomal context. Studies carried out in vivo indicate that SWI/ SNF is recruited to double-strand break sites (Chai et al, 2005), and the inactivation of the SWI/SNF complex results in inefficient DNA double-strand break repair in vivo (Park et al, 2006).…”
mentioning
confidence: 99%
“…In vitro studies showed that the SWI/SNF complex enhances the incision and excision steps by purified NER proteins in reconstituted nucleosomes with DNA containing UV-induced lesions. 118,119 SWI/SNF also appears to act in vivo during NER, where it is at least partially responsible for increasing DNA accessibility in the repressed MFA2 promoter following UV treatment. 120,121 Snf6 and Snf5, two subunits of the SWI/SNF complex, interact with NER damage recognition Rad4-Rad23 proteins.…”
Section: © 2 0 0 9 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%